PERBANDINGAN STRATEGI PEMASARAN POLITIK PADA PEMILIHAN KEPALA DAERAH DI KABUPATEN KENDAL TAHUN 2010 DAN BATANG TAHUN 2011 STUDI KASUS PADA PASANGAN YAKIN DAN BERSUSILA - Nur Muhibbatul Ulya; Muhammad Adnan; Priyanto Harsasto (Journal of Politic and Government Studies, 2014)
General election widely followed by the incumbent candidate, as it did in election disctrict regional head in Kendal at year 2011 and Batang at year 2012, in which one candidate is the wife of the regent 2 previous period and the two regents were eventually convicted of corruption . The purpose of the study was to determine the political marketing of YAKIN and BERSUSILA, and the factors that influence YAKIN victory and the factors that influence defeat bereft of BERSUSILA.This type of research is qualitative, where the information is obtained from the prospective candidates, team succession, and the voting public through interviews. Data were analyzed using qualitative analysis with content analysis approach .The results of the study are (1) that political marketing is done by YAKIN and BERSUSILA basically not much different. (a) Segmentation relatively equally YAKIN and BERSUSILA. YAKIN more than support elements of society bereft of decency. YAKIN and BERSUSILA are equally promoted by political parties PDIP. Strategies used by YAKIN and BERSUSILA to demonstrate competence and charisma themselves with education degrees and titles include religion, as well as using religious accessories. YAKIN and BERSUSILA also visited religious leaders and raise the issue of gender. Strategies YAKIN and BERSUSILA get swing voters are forming a map of the vote, a solid area, less, and will be lost, as well as form a coalition (b) YAKIN and BERSUSILA sound alike targeting at least 50 % by district with the focus of the campaigns in the villages. (c) In general, the products politics of YAKIN and BERSUSILA not much different. Common vision and mission impressed and difficult to apply. YAKIN and BERSUSILA also uses general pattern and not something new. YAKIN and BERSUSILA are equally trying to portray themselves as a couple of candidates who have a strong faith and a personal meet the requirements of Islam. They also "sell" women as regent candidate. Susi imaged as a mature woman, motherhood, and still beautiful at the age has begun to dusk. Widya and Susi have relatively similar track record to have a husband who served as regent for 2 periods and exposed cases of corruption, and is Chairman of DPC PDIP. However YAKIN regarded track record tends to support the victory than BERSUSILA of the high level of education and have experience of organizing, as well as more widely supported YAKIN mass organizations. While the fake diploma case stumbles BERSUSILA political money making track record worse. Promotion is done YAKIN relatively similar with BERSUSILA, which is much use of advertising banners and billboards . However YAKIN better able to optimize the PR compared bereft of decency. YAKIN and BERSUSILA relatively the same4during the debate, which is normal. YAKIN political costs lower BERSUSILA, though the cost of the biggest expenses is used for operational costs and the media. The number of personnel involved in the campaign well YAKIN and BERSUSILA relatively the same, have the same communication between teams, and solidity are both in implementation.YAKIN equally owned optimize social networking, as well as conduct allegedly involved in money politics. (2) Factors affecting YAKIN victories include the popularity and Mustamsikin Widya, suitability Widya - Mustamsikin pair that complements in terms of the ideology of the party and the masses, a high level of education, political party vehicles (PDI-P), the optimal use of public relations, the use of network social good, money politics, and a solid succession team. (3) Factors affecting among other defeats YAKIN and BERSUSILA Susi-Lufran less popular, Susi image decreases as fake diploma case and money politics, less optimizing PR, and less solid succession team.Suggestions research is necessary to develop a team succession campaign techniques that are creative alternatives and benefits can be felt directly by the public, so that the cost of political campaigns are not wasted. In addition it is necessary to develop techniques that are providing education campaign politics to society, so that no conflicts easily arise due to differences in political choices.Keywords: political marketing, segmentation, targeting, political product, incumbent, YAKIN, BERSUSILA